2016
DOI: 10.4155/bio-2016-0057
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of 18 Amino Acids in Human Plasma: Application in Renal Transplant Patient Plasma by Targeted UHPLC–MS/MS

Abstract: The method was successfully applicable for amino acid analysis in the renal transplant patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In spite of the established association between plasma AA concentrations with estimated glomerular filtration rate (eGFR) in transplantation patients 13 , little information was available about the value of AA profile in prediction of AKI among patients receiving the renal transplantation. Furthermore, our previous research revealed that concentrations of total AAs and many AAs, such as alanine, lysine, aspartic acid, serine, and methionine, were significantly altered in renal transplantation patients when compared to the healthy volunteers 14 . This finding shed light on the meaning of the AA profile in renal transplantation patients, characterization of which would be necessary for understanding AKI process and identifying potential biomarkers for kidney dysfunction.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In spite of the established association between plasma AA concentrations with estimated glomerular filtration rate (eGFR) in transplantation patients 13 , little information was available about the value of AA profile in prediction of AKI among patients receiving the renal transplantation. Furthermore, our previous research revealed that concentrations of total AAs and many AAs, such as alanine, lysine, aspartic acid, serine, and methionine, were significantly altered in renal transplantation patients when compared to the healthy volunteers 14 . This finding shed light on the meaning of the AA profile in renal transplantation patients, characterization of which would be necessary for understanding AKI process and identifying potential biomarkers for kidney dysfunction.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, we herein present a quantitative method of 25 AAs in plasma samples by ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC–MS/MS) 14 , which was based on modification of our previously published method. Furthermore, the targeted metabolomics study was conducted in 42 patients underwent renal transplantation with/without acute kidney injury and 24 healthy volunteers, in a single-center retrospective observational study.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, liquid chromatography-tandem mass spectrometry (LC-MS/MS) has been adopted for amino acid analysis in physiological samples due to its excellent selectivity and sensitivity. [13][14][15][16][17][18] However, co-eluting endogenous compounds in the matrix interferes with ionization efficiency and reproducibility of the ionization source. To enhance the detection sensitivity and chromatographic retention, derivatization reagents such as o-phthaldialdehyde and 9-uorenylmethyl chloroformate were applied.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, usage of HILIC with MS detection to amino acids in biological matrix, as well as clinic samples such as urine, plasma and serum have been successfully applied. 17,18 However, to our knowledge, few reports refer the analysis of amino acids in human tears through HILIC coupled with high resolution mass spectrometry. 4 In this study, we developed a liquid chromatography high resolution mass spectrometry method for the simultaneous determination of 15 amino acids (AAs) in human tears.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, various analytical techniques including nuclear magnetic resonance (NMR) (Schicho et al, ; Stoop et al, ), capillary electrophoresis, gas chromatography and liquid chromatography (LC), combined with various detection systems, such as fluorescence detection, ultraviolet detection, electrochemical detection and mass spectrometry (MS), have been developed for quantification of AAs in the biological fluids (Hirayama & Soga, ; Poinsot, Ong‐Meang, Gavard, & Couderc, ; Kvitvang, Andreassen, Adam, Villas‐Bôas, & Bruheim, ; Chen et al, ; Peris‐Vicente, Gimeno Adelantado, Carbó, Castro, & Reig, ; Rodier et al, ). Because most AAs show high polarity with low molecular weight, a derivatization step is often applied to achieve better retention on the reversed‐phase column (Armenta et al, ; Kaspar et al, ; Sánchez‐López, Crego, & Marina, ; Wang et al, ). For example, Thomas Themelis et al determinated glutathione using 1,4‐naphthoquinione as a derivazation reagent (Themelis, Gotti, & Gatti, ).…”
Section: Introductionmentioning
confidence: 99%